2021
DOI: 10.4314/ahs.v21i2.33
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between cardiovascular signs and neurological signs in asphyxiated neonates in Ilorin, North Central Nigeria

Abstract: Background: Perinatal asphyxia is a condition associated with multiple organ dysfunctions inclusive of cardiovascular dys- function. Neurologic predictors of survival have been studied, but little has been reported regarding cardiovascular signs and their role in determining outcome in asphyxia. Objective: The study aimed to determine the relationship between cardiovascular signs and outcomes in asphyxiated new- borns with hypoxic ischaemic encephalopathy. Methods: This was a cross sectional study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…However, cooling has not shown consisted outcomes especially from LMIC. 44 Three-quarters of neonates with an Apgar score of 0-3 at the 5 th minute died, this was significantly associated with an increase in death at the univariate level, which is similar to findings by Casey et al 45 who found a significant increase of mortality within 28 days of life in neonates with 5 minute Apgar score of 0-3, compared to less than 1% in those with a score of 4-6. 43 However, the Apgar score was not found to be a predictor of death at the multivariate level after adjusting for confounders.…”
Section: Articlesupporting
confidence: 86%
“…However, cooling has not shown consisted outcomes especially from LMIC. 44 Three-quarters of neonates with an Apgar score of 0-3 at the 5 th minute died, this was significantly associated with an increase in death at the univariate level, which is similar to findings by Casey et al 45 who found a significant increase of mortality within 28 days of life in neonates with 5 minute Apgar score of 0-3, compared to less than 1% in those with a score of 4-6. 43 However, the Apgar score was not found to be a predictor of death at the multivariate level after adjusting for confounders.…”
Section: Articlesupporting
confidence: 86%
“…Now to the clinical. Nigerian clinicians have a paper on the relationships between ‘cardiovascular signs and neurological signs in asphyxiated neonates.’ 32 This paper is followed by several on sickle cell anemia: ‘the burden of iron overload among non-chronically blood transfused preschool children 33 ; disease severity and folate status 34 ; utilization and provider-related barriers to the use of hydroxyurea in the treatment of sickle cell disease patients, 35 and psycho-social problems of adolescents with sickle-cell anaemia. 36 The section ends with an interesting blood transfusion paper on the utility of ‘home-made’ reagent red blood cells for antibody screening during pre-transfusion compatibility testing in Uganda.…”
mentioning
confidence: 99%